Employability competences through short-term intensive PBL-events in higher education - Wyke, Simon; Jensen, Annie Aarup; Krogh, Lone; Ravn, Ole; Svidt, Kjeld (Frontiers in Education, 2022)
The article presents a three-day Problem Based Learning (PBL) event taking place as an interdisciplinary, cross-institution and cross-sector digital learning activity in architecture, engineering, and construction (AEC). Students were given an overall realistic task by a builder to solve in interdisciplinary teams consisting of members from the involved institutions, i.e., a university college, a university, and a vocational school. Representatives from the AEC industry acted as consultants and teachers from the involved institutions acted as supervisors. Besides drawing on students’ existing disciplinary knowledge and skills, their skills in project management, collaboration and communication were further enhanced by the event. Coming from a university with a PBL-model of semester-long project work, our main research interest focused on the university students’ learning experience during this very short PBL learning activity. When studying the event from a work based learning perspective (Eraut 2011) we found that the students’ experiences and competences developed during the course of the event to a large extent could be interpreted as employability competences, thus placing the event as a ‘transitional’ activity between education and a future work place. Furthermore, we found that the gain from the event was mutual – the industry representatives learned about new digital solutions and programs and gained insights into the study programs’ curriculum and disciplinary scope. The empirical research was based on qualitative methods involving semi structured interviews (students as well as industry representatives), supplemented with informal conversations, observations, and photo documentation.